Simple and cost-effective polycondensation routes to antimicrobial consumer products. Issue 23 (18th May 2016) - Zhang, Musan; Teo, Jye Jyn; Liu, Shaoqiong; Liang, Zhen Chang; Ding, Xin; Ono, Robert J.; Breyta, Gregory; Engler, Amanda C.; Coady, Daniel J.; Garcia, Jeanette; Nelson, Alshakim; Yang, Yi Yan; et al.
Abstract : Cost-effective macromolecular antimicrobials were synthesized to explore a variety of chemical functional groups that target antimicrobial performance and reduce cytotoxicity. Abstract : In this study, cost-effective macromolecular antimicrobials for applications in consumer care products were targeted. Our strategy for inexpensive yet highly efficacious macromolecular antimicrobials employs organocatalytic step-growth polymerization of commercially available monomers and catalysts. Importantly, bulk polymerization conditions were sought to mitigate the cost, reduce solvent waste, and eliminate polymer purification and isolation steps. Moreover, diffusion-controlled, bulk polymerization conditions limited the polymer number-average molecular weights ( M n ) to ∼5000–10 000 g mol −1, as the activity and selectivity was independent of molecular weight. The modest molecular weights enable the polymers to be soluble/processable for subsequent quaternization. A number of polymer-forming reactions were investigated including ester, amide, urea, and guanidinium formation. Of these polymers, polyamides quaternized with methyl iodide or benzyl bromide exhibited excellent water-solubility and potent antimicrobial activity against a panel of clinically relevant microbes including multidrug-resistant P. aeruginosa . These polymers contain amide bonds, which remain intact in aqueous solution (even in a weakly alkaline environment), thereby increasing their suitability for personal care products due to the long shelf-life. The introduction of Jeffamine to the polymers as a means to further reduce cost does not change antimicrobial potency, but significantly increases compatibility to mammalian cells, further justifying its potential use in personal care products. The advantages of this approach addresses not only the cost-related challenges of polymerization scale-up, but also the synthetic versatility necessary to explore a variety of chemical functional groups and tune the polymer amphiphilicity for targeted antimicrobial performance, as well as cytotoxicity.